Effects of COVID-19 Confinement on the Health and Perspectives of Exercise Practice in Portugal - Loureiro, Nuno; Murta, Luís; Bento, Pedro; Loureiro, Vânia (Arena-Journal of Physical Activities, 2022)
Introduction: Social confinement, imposed by the SARS-CoV-2 coronavirus, was an extraordinary situation and implied several consequences on people’s health, which are still not fully understood. This study aimed to understand the changes in mental health and to determine the probability of returning to sports practice during the period of generalized confinement and lockdown due to COVID-19, between January and March 2021. Methods: A self-administered on online survey (PEF-COVID19) was applied to the general Portuguese population, aged 18 years. The t-test for paired samples and the chi-square test were used to analyze the variables, p < 0.05. Results: 811 participants filled the questionnaire and 666 were included. Our study showed that during confinement: (i) there was an increase of anxiety (before - M= 3.1 ± 2.1; during – M= 4.3 ± 2.7) and stress (before – M = 3.1 ± 2.5; during – M= 4.1 ± 3) and (ii) a greater probability of dropping out sports practice (before – M = 1.1 ± 2; during – M= 7.5 ± 3.3).Conclusions: The results demonstrate that the period of confinement and lockdown, significantly influenced health and the intention to remain practicing sports. These indicators demonstrate the need to develop quality sports/exercise programs, adjusted to different target groups, especially the most vulnerable, to keep the population active, reduce sedentary time and the consequent impacts on mental and physical health.